A Novel Cerium Tungstate Nanosheets Modified Electrode for the Effective Electrochemical Detection of Carcinogenic Nitrite Ions. Issue 10 (20th July 2017) - Vinoth Kumar, J.; Karthik, R.; Chen, Shen‐Ming; Balasubramanian, P.; Muthuraj, V.; Selvam, V.
Abstract: In this present scenario, for the first time, we propose a facile and simple wet chemical approach for the fabrication of two‐dimensional (2D) cerium tungstate (CeW2 O9 ;CeW) nanosheets and evaluated as an electrochemical sensor for the detection of nitrite ions. The successful formation of CeW2 O9 nanosheets was confirmed by various physicochemical techniques such as X‐ray diffraction, Fourier transform infrared spectroscopy, Raman, Scanning electron microscope, Transmission electron microscope and Energy dispersive X‐ray studies. The electrochemical properties of the CeW nanosheets were studied by using cyclic voltammograms (CV) and chronoamperometric techniques. As an electrochemical sensor, the CeW nanosheets modified glassy carbon electrode (GCE) showed superior electrocatalytic activity in the oxidation of nitrite in terms of higher anodic peak current and lower oxidation potential when compared with unmodified GCE. CeW nanosheets based electrochemical sensor has been fabricated which detect nitrite in wide linear response range, good sensitivity and very low detection limit of 0.02–986 μM, 2.85 μA μM −1  cm −2 and 8 nM, respectively. Moreover, the CeW nanosheets modified GCE exhibited excellent selectivity even in the presence of common metal ions and biologically co‐interfering compounds. For the practical viability of the prepared amperometric sensor has been utilized in various water samples such as tap, lake and drinking water and the obtained recoveries are appreciable. Abstract :